Synthesis And Characterization Of Magnesium Oxide Nanomaterials Via Direct Heating Method - Kok, Kai Lin (Universiti Sains Malaysia, 2022)
As nanomaterials become increasingly inevitable in everyday life applications, various kinds of synthesis methods have been developed to produce nanomaterials with different morphologies and characteristics. Metal oxides nanomaterials have been one of the attractive materials to be synthesized for the application of photodegradation, due to the severe environmental pollution in recent years. MgO nanomaterials are one of the promising materials that can be used as photocatalysts. This project aims to synthesize MgO nanomaterials via the newly developed Direct Heating (DH) method on the surface of the kanthal wire that provide certain support to avoid massive loss of nanomaterials during application for instance wastewater treatment process. This project studied the effects of types of precursors i.e. Mg(NO3)2, PEG 200, NH3 (Type 1), MgCl2, NaOH (Type 2) and Mg(NO3)2, NaOH (Type 3), heating duration (i.e. 0, 5, 15, 30, 45, and 60 min) and heating power (i.e. 0, 10, 20, 30, 40, 50 W) for the growth of MgO nanomaterials on kanthal wires. The XRD, FTIR, and TEM proved the presence of MgO nanomaterials, indicating the success of developing the DH method to synthesize MgO nanomaterials. The optimized synthesis condition to produce MgO nanomaterials was using Type 3 precursor and 50 W heating power for 45 min. This was because this synthesis condition produced MgO nanorods (diameter ~74.97 nm, length of ~184.98 nm), and good surface coverage (92.05%). The photodegradation efficiency of these MgO nanorods under UV irradiation was 34.53%.